Intelligent modeling of thermal processes in wood: a systematic review - Zullo Godinho, Emmanuel; Marques Barreiros, Ricardo; Fernando Gouvêa, Cantídio; Dartiere Zulian Fermino, Caetano (Revista Brasileira de Engenharia de Biossistemas, 2026)
This study mapped the state of knowledge on the applicability of Neuro-Fuzzy approaches to wood thermal modification through a Systematic Literature Review (SLR) reported according to PRISMA recommendations. Searches were performed in major databases and, after screening and eligibility assessment, 26 peer-reviewed articles were included. The evidence shows that Neuro-Fuzzy methods are widely applied to industrial modeling and optimization; however, no studies were identified that directly apply Neuro-Fuzzy/ANFIS to the specific process of wood thermal modification within the scope of this review. This finding indicates an evidence gap and supports a research agenda focused on reproducible data pipelines (e.g., Python) and integrated databases of thermally modified wood properties to enable future Neuro-Fuzzy modeling and optimization in the forestry sector.